Investigate the possibility of using carbon onion nanolubrication with DLC cutting tool to reduce the machining power consumption - Sarhan, Ahmed Aly Diaa Mohammed; Ooi, M.E.; Sayuti, M.; Abd Shukor, Mohd Hamdi (2014)
Due to rapid consumption of world's fossil fuel resources and impracticality of large-scale application and production of renewable energy, the significance of energy efficiency improvement of current available energy modes has been widely realized by both industry and academia. In the CNC machining field, the key solution for this issue is by increasing the effectiveness of the existing lubrication systems as it could reduce the power required to overcome the friction component in machining process. For more improvement, introducing the nanolubrication could produce much less power consumption as the rolling action of billions units of nanoparticle in the tool chip interface could reduce the cutting forces significantly. In this research work, the possibility of using carbon onion nanolubrication with DLC cutting tool is investigated to reduce the machining power consumption. Carbon onion nanolubrication has been successfully developed with high tribology performance and mixed with ordinary mineral oil. The proper sonification method is used to provide a way to mix and suspend the particles thoroughly and efficiently. Furthermore, Diamond-like carbon (DLC) cutting tool is used and expected to play significant role in reducing friction and cutting forces and increasing abrasion resistance. The results showed significant reduction of the cutting force and the working power compared with the other conditions of using carbon black and normal lubrication systems.